METHODS OF IMPROVING ORTHOGRAPHIC LITERACY THROUGH WORKING ON PARTS OF SPEECH IN MOTHER TONGUE LESSONS IN PRIMARY GRADES (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the pedagogical and methodological foundations of organizing activities related to parts of speech in mother tongue lessons aimed at improving the orthographic literacy of primary school pupils. The paper highlights methods for the conscious mastery of spelling rules and the formation of grammatical and orthographic skills through teaching parts of speech. In addition, the influence of a system of exercises and tasks, interactive methods, and practice-oriented approaches on students’ literacy is scientifically and practically substantiated.